Dissecting the Role of Dominance in Robberies: An Analysis and Implications for Microsociology of Violence - Liebst, Lasse Suonperä (Journal of interpersonal violence, 2021)
The influential microsociological theory of violence advanced by Randall Collins suggests that emotional dominance preconditions physical violence. Here, we examine robbery incidents as counterevidence of this proposition. Using 50 video clips of real-life commercial robberies recorded by surveillance cameras, we observed, coded, and analyzed the interpersonal behaviors of offenders and victims in microdetail. We found no support for Collins’s hypothesized link between dominance and violence, but evidence against it instead. It is the absence, not the presence, of emotional offender dominance that promotes offender violence. We consider these results in the light of criminological research on robbery violence and suggest that Collins’s strong situational stance would benefit from a greater appreciation of instrumental motivation and cold-headed premeditation.